CYTOGENETIC EFFECTS OF THE CRUDE SAPONINS OF Yucca elephantipesL. LEAVESONTHE Allium cepa L. ROOT TIPS MITOSIS. - & Najem, Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to investigate cytogenetic effects of the crude saponinsof Yucca elephantipes leaves on mitosis. The root tips of Allium cepa L. were used as plant test system in vivo. Root tips of A. cepa were tested for four hours with four concentrations of the crude saponins (0.00, 6.25, 12.5, 25 or 50 mg/ml). This study were included some cytogenetic diagnosis included mitotic index, phase index, and chromosomal aberration. Results showed that saponins reduced the mitotic index (MI) to less than 50%, specifically when treated with 12.5,25 or 50 mg/ ml mitotic index reached 25.48, 17.98, 18.81% respectively, this reduction was considered toxic and sub lethal. Saponins arrested chromosomes at metaphase (c-metaphase) up to 100% at 6.25 mg/ml and chromosomal aberrations including micronuclei and nuclear lesion (chromatin lesion) in prophase and interphase at the concentrations 25 and 50 mg/l recorded 1.30-8.30%.